1990
DOI: 10.1056/nejm199010043231404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Ileal Bypass Surgery on Mortality and Morbidity from Coronary Heart Disease in Patients with Hypercholesterolemia

Abstract: Partial ileal bypass produces sustained improvement in the blood lipid patterns of patients who have had a myocardial infarction and reduces their subsequent morbidity due to coronary heart disease. The role of this procedure in the management of hypercholesterolemia remains to be determined. These results provide strong evidence supporting the beneficial effects of lipid modification in the reduction of atherosclerosis progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
205
0
16

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 925 publications
(229 citation statements)
references
References 47 publications
3
205
0
16
Order By: Relevance
“…When comparing statin and non-statin lipid-lowering trials, statin-treatment trials demonstrate benefits within 5 years compared with greater than 7 years for non-statin trials [28,29]. Furthermore, subgroup analysis of WOSCOPS and CARE studies indicate that, despite comparable serum cholesterol levels among patients in the statin and placebo groups, patients who are treated with statin have 47% lower risk of developing subsequent events [2,4].…”
Section: Clinical Trials With Statinsmentioning
confidence: 99%
“…When comparing statin and non-statin lipid-lowering trials, statin-treatment trials demonstrate benefits within 5 years compared with greater than 7 years for non-statin trials [28,29]. Furthermore, subgroup analysis of WOSCOPS and CARE studies indicate that, despite comparable serum cholesterol levels among patients in the statin and placebo groups, patients who are treated with statin have 47% lower risk of developing subsequent events [2,4].…”
Section: Clinical Trials With Statinsmentioning
confidence: 99%
“…Procedures without gastric restriction, such as intestinal bypass or duodenal bypass, can produce only a minimal weight loss 101. VBG was the first successful bariatric procedure with a pure gastric restriction effect.…”
Section: Understanding the Mechanismmentioning
confidence: 99%
“…Most of these tiñáis have shown slowing or arrest of progression of coronary atherosclerosis. Reports concerning femoral atherosclerosis are more scarce [7,[14][15][16]21,24,25], In several recent clinical trials on plasma lipid regu lation, measurements of carotid artery intima-media thickness (IMT) have been included, because coro nary and carotid atherosclerosis share coronary events as their major cause of morbidity and mortality [38][39][40][41]. Indeed, most of these studies have also shown a slowing of progression of IMT during lipid-lowering treatment.…”
Section: Introductionmentioning
confidence: 99%